Shari’ah Analytics of Arabic Currency Terms and Implications for Cryptocurrency - Fahmi Ali Hudaefi; Muhammad Zakiy; Abdelkader Laallam; Fauzul Hanif Noor Athief; Muhamad Subhi Apriantoro (Journal of Islamic Monetary Economics and Finance, 2026)
This study introduces Sharīʿah analytics, a novel methodological framework leveraging machine learning and big data analytics, to systematically analyze classical Islamic jurisprudential texts (furūʿ al-fiqh kitābs), and further assesses cryptocurrencies against the Islamic monetary principles. Sharīʿah analytics is done via computationally processing 55 texts across four Sunni and one Shia legal tradition, examining Arabic currency-related terms and their fundamentals to explain whether cryptocurrencies align with pre-modern juristic definitions rooted in physicality, standardization, and regional acceptance. Findings reveal that cryptocurrencies inherently diverge from classical criteria, e.g., weight-based valuation, intrinsic material purity, and communal consensus, interpreting them non-compliant with traditional Islamic currency frameworks. This approach advances Islamic monetary scholarship, offering a data-driven lens to reconcile ethical monetary principles with emerging digital economies. The study fills a gap in existing literature by systematically contextualizing cryptocurrency debates within primary juristic sources rather than relying on speculative analogies or fragmented scholarly opinions. Acknowledgment Fahmi Ali Hudaefi would like to thank Dr Haula Noor (Universitas Islam Internasional Indonesia) for introducing him to Islamicate Digital Humanities, which grounds the idea of Shariah analytics. This research received funding from the Deanship of Scientific Research, Vice Presidency for Graduate Studies and Scientific Research, King Faisal University, Saudi Arabia [KFU252890]. In addition, this research also received funding from Majelis Pendidikan Tinggi Penelitian dan Pengembangan (Diktilitbang) Muhammadiyah Risetmu Penelitian Reguler Batch IX [0259.1043/I.3/D/2025].